Internat Kresowy w Bydgoszczy 1920-1936 (Kronika Bydgoska, 2013)
Internat Kresowy in Bydgoszcz was created in the second half of 1920, on the initiative of the Society for Children and Youth in the Eastern Borderlands. Internat Kresowy took care of boys aged 12 to 20 years, mostly orphans who lost their parents during the war and revolution in the former eastern territories of Poland. Boys also admitted that relatives, because of the loss of property in the East could not afford to maintain them. As well as former soldiers whose education was interrupted by the Polish-Bolshevik war. Pupils lived in the building of the former German orphanage at Senatorska 80 (now St. Chodkiewicza 32), and learned, among other things in the School of Humanities and the Municipal School of Mathematics and Natural Sciences, and the National School of Arts and Crafts. For the first four years, Internat Kresowy was a dramatic financial situation. If not for the support of the support of the landowners Pomerania and Wielkopolska, and thanks to the kindness borderland landowners now living in Bydgoszcz facility could not be run. Since 1925, thanks to government subsidies and reorganization, the situation has improved significantly. Internat Kresowy was an important point on the cultural map. This was prepared for concerts and performances for Bydgoszcz inhabitants. In the 30s former pupils took care of students from poor families living in their district-Bielawy. In its first year, 247 boys lived in the boarding school. With each passing year the number is decreasing. After sixteen years of the mission of the Society for Children and Youth in the Eastern Borderlands September 15, 1936 agreement with the city to lease the building has been terminated. Internat Kresowy ceased to exist.